The use of Jigsaw Strategy to Improve Students' Speaking Achievement at SMKN 4 Palembang - Angelita, Helen; Iman, Jaya Nur; Permana, Dio Resta (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2026)
Speaking ability plays a central role in English learning, yet many vocational high school students still struggle with issues such as restricted vocabulary, low self-confidence, and insufficient opportunities to practice. This research was conducted to investigate how far the Jigsaw technique can contribute to enhancing students’ speaking performance. The study employed a quasi-experimental approach involving two groups of learners: the experimental group, which received lessons through the Jigsaw strategy, and the control group, which was instructed using conventional teaching. The participants consisted of 68 tenth-grade students of SMKN 4 Palembang. Data were obtained from pre-test and post-test activities and were analyzed through paired sample t-test and independent sample t-test. The analysis demonstrated that the experimental group showed a meaningful improvement in speaking ability (Sig. 0.002 < 0.05), whereas the control group did not reach significant progress (Sig. 0.103 > 0.05). Furthermore, the independent sample t-test confirmed that there was a notable difference in achievement between the two groups (Sig. 0.008 < 0.05). Based on these results, it can be concluded that applying the Jigsaw strategy has a positive and effective impact on students’ speaking achievement, making it a recommended method in vocational high school English classrooms.